Forward trading and collusion of firms in volatile markets - Markus F. Aichele (University of Tübingen, Faculty of Economics and Social Sciences, 2014)
Commodity markets are characterized by large volumes of forward contracts as well as high volatility. They are often accused of weak competitive pressure. This article extends the existing literature by analyzing tacit collusion of firms, forward trading and volatility simultaneously. The expected collusive pro t may depart from the monopoly outcome in a volatile market (Rotemberg and Saloner, 1986). Introducing forward trading enables firms to gain the expected monopoly pro t for a broader range of parameters. In contrast to a deterministic market (Liski and Montero, 2006), trading forward in a volatile market may lead to an expected collusive pro t below the monopoly one.
urn:nbn:de:bsz:21-dspace-574637
Keywords: L13; 330; Industrial organization; Forward trading; Collusion; Energy Markets